2010
DOI: 10.1371/journal.pbio.1000540
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na+/K+ ATPase Transport Velocity by RNA Editing

Abstract: Editing of Na+/K+ ATPase mRNAs modulates the Na+/K+ pump's turnover rate by selectively targeting the release of the final sodium to the outside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
(58 reference statements)
0
28
0
1
Order By: Relevance
“…For example, two messages encoding voltage-dependent potassium channels in Doryteuthis pealeii and Doryteuthis opalescens (formerly known as Loligo pealeii and Loligo opalescens) exhibited over 30 individual recoding sites (Patton et al, 1997;Rosenthal and Bezanilla, 2002). Subsequent studies on mRNAs encoding other ion channels, ion pumps and ADARs in squid revealed as many recoding editing sites in these few messages as had been identified in the entire human transcriptome (Colina et al, 2010;Liu et al, 2001;Palavicini et al, 2009;Pinto et al, 2014;Ramaswami and Li, 2014;Ramaswami et al, 2013;Rosenthal et al, 1997). It seemed unlikely that the squid studies happened upon highly edited messages by chance.…”
Section: Cephalopod Rna Editing Breaks the Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, two messages encoding voltage-dependent potassium channels in Doryteuthis pealeii and Doryteuthis opalescens (formerly known as Loligo pealeii and Loligo opalescens) exhibited over 30 individual recoding sites (Patton et al, 1997;Rosenthal and Bezanilla, 2002). Subsequent studies on mRNAs encoding other ion channels, ion pumps and ADARs in squid revealed as many recoding editing sites in these few messages as had been identified in the entire human transcriptome (Colina et al, 2010;Liu et al, 2001;Palavicini et al, 2009;Pinto et al, 2014;Ramaswami and Li, 2014;Ramaswami et al, 2013;Rosenthal et al, 1997). It seemed unlikely that the squid studies happened upon highly edited messages by chance.…”
Section: Cephalopod Rna Editing Breaks the Rulesmentioning
confidence: 99%
“…For example, editing sites in mRNAs encoding squid potassium channels alter kinetics, subunit tetramerization and surface expression levels (Patton et al, 1997;Rosenthal and Bezanilla, 2002). A site in a mRNA encoding a Na + /K + -ATPase α-subunit increases the rate of ion pumping using a novel mechanism (Colina et al, 2010). At negative membrane potentials like the resting potential, the Na + /K + -ATPase's ability to pump Na + ions out of the cell is inhibited by both voltage and the high extracellular Na + concentration.…”
Section: Cephalopod Rna Editing Breaks the Rulesmentioning
confidence: 99%
“…As expected from a mechanism that can recode almost half of all codons, the effects of RNA editing on protein function are diverse (8). The beststudied examples come from mRNAs encoding elements of the machinery for excitability in the nervous system, where editing changes ion selectivity of ionotropic glutamate receptors, G-protein coupling of metabotropic serotonin receptors, inactivation of a voltage-dependent K + channel, and the transport rate of a Na + /K + ATPase, among other things (9)(10)(11)(12). Because of its versatility, the ability to control RNA editing could prove useful for medicine and basic research.…”
mentioning
confidence: 99%
“…Two consequences of the unequal transport stoichiometry of Na þ and K þ are that steady pumping produces an outwardly directed current (1), proportional in magnitude to the turnover rate (2), which can be monitored electrically (3)(4)(5)(6)(7)(8), and that at least one step in the transport cycle must move charge through the membrane field (9). The latter implies that, under favorable conditions, charge relaxations following voltage jumps can be used to learn details about specific steps during the transport cycle (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%